2002
DOI: 10.1152/jn.2002.88.4.1915
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Activity of a CPG Neuron After the Reinforcement of an Operantly Conditioned Behavior inLymnaea

Abstract: We have previously shown that the aerial respiratory behavior of the mollusk Lymnaea stagnalis can be operantly conditioned, and the central pattern generating (CPG) neurons underlying this behavior have been identified. As neural correlates of operant conditioning remain poorly defined in both vertebrates and invertebrates, we have used the Lymnaea respiratory CPG to investigate neuronal changes associated with the change in behavior after conditioning. After operant conditioning of the intact animals, semi-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 26 publications
5
65
0
Order By: Relevance
“…In addition, we have demonstrated that: (1) memory recall is context specific (Haney and Lukowiak, 2001); (2) one-trial learning occurs (Martens et al, 2007); (3) reconsolidation and extinction occur (Sangha et al, 2003a,b); (4) forgetting is an active process ; and (5) a false memory can be implanted into the snail following activation of the memory . We have also shown that: (1) a single neuron, RPeD1 is a necessary site for LTM formation (Scheibenstock et al, 2002) and significant changes in synaptic input as well as changes in neuronal excitability of this neuron have been correlated with LTM (Spencer et al, 1999(Spencer et al, , 2002Braun and Lukowiak, 2011); (2) learning and memory formation can be demonstrated in an in vitro semi-intact preparation (McComb et al, 2005); (3) differences in cognitive ability occur at both the behavioural (Orr et al, 2009;Dalesman et al, 2011a,b,c) and neuronal levels Braun et al, 2012); and (4) a partial proteomics profile exists for changes underlying LTM formation . Finally, a number of environmentally relevant stressors either enhance or block memory formation .…”
Section: Introductionmentioning
confidence: 80%
“…In addition, we have demonstrated that: (1) memory recall is context specific (Haney and Lukowiak, 2001); (2) one-trial learning occurs (Martens et al, 2007); (3) reconsolidation and extinction occur (Sangha et al, 2003a,b); (4) forgetting is an active process ; and (5) a false memory can be implanted into the snail following activation of the memory . We have also shown that: (1) a single neuron, RPeD1 is a necessary site for LTM formation (Scheibenstock et al, 2002) and significant changes in synaptic input as well as changes in neuronal excitability of this neuron have been correlated with LTM (Spencer et al, 1999(Spencer et al, , 2002Braun and Lukowiak, 2011); (2) learning and memory formation can be demonstrated in an in vitro semi-intact preparation (McComb et al, 2005); (3) differences in cognitive ability occur at both the behavioural (Orr et al, 2009;Dalesman et al, 2011a,b,c) and neuronal levels Braun et al, 2012); and (4) a partial proteomics profile exists for changes underlying LTM formation . Finally, a number of environmentally relevant stressors either enhance or block memory formation .…”
Section: Introductionmentioning
confidence: 80%
“…EXT or Ext, Extinction; PRE, pretest period; Con, control; Exp, experimental. involve changes in the biophysical properties or synaptic connections of the L25 and R25 neurons, which are the major elements of the pattern generator for the contractions (Byrne and Koester, 1978;Byrne, 1983;Koester, 1989), and changes in the frequency of spontaneous contractions could involve changes in the firing or effects of the peptidergic modulatory neurons R15 and R20 (Alevizos et al, 1989(Alevizos et al, , 1991, which produce slow excitation of the L25 and R25 neurons. Such changes in the properties of neurons in a central pattern generator are thought to contribute to operant conditioning of feeding in Aplysia (Nargeot et al, 1999a,b;Brembs et al, 2002) and may also contribute to operant conditioning of aerial respiration in Lymnea (Spencer et al, 1999(Spencer et al, , 2002Scheibenstock et al, 2002). Because the gill often appears to contract just before it reaches the criterion level during training (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The accounts of the underlying neurobiology include the differential requirements of local translation and transcription for intermediate-and long-term memory, respectively, as well as neural correlates in neurons in the CPG [46 ,49 ,55,56 ]. Importantly, the CPG activity initiating neuron RPeD1 (right pedal dorsal 1; see Figure 3d) shows a lower spontaneous firing frequency in semi-intact preparations from trained animals after a brief reminder training [56 ]. In isolated ganglia of operantly trained animals, RPeD1 is quiescent more often than in preparations from yoked control animals, and the efficacy of the excitatory connection from RPeD1 to IP3 (input 3 interneuron; see Figure 3d) is reduced [55].…”
Section: Operant Conditioning Of Aerial Respiratory Behavior In Lymnaeamentioning
confidence: 98%